Abdominal Epilepsy as Sequelae of COVID-19 in a Patient With Granulomatosis and Polyangiitis - José Joel Parada-Jiménez; Juan de Dios Albavera-Peña (Annals of Internal Medicine: Clinical Cases)
Abdominal epilepsy is characterized by chronic abdominal pain, and an epileptogenic focus in the temporal lobe is found in most patients. Here, we present a patient case of a 60-year-old woman hospitalized because of several episodes of epigastric pain preceded by visual and auditory hallucinations 1 month after having had COVID-19. The electroencephalogram obtained during an episode of pain showed temporo-occipital epileptiform activity. Infection by SARS-CoV-2 has been associated with neurologic disorders including epilepsy and, in this case, abdominal epilepsy.